Copper‐catalyzed C‐N coupling reaction of tosylhydrazones. (4th July 2018) - Wu, Xufeng; Li, Lingyu; Jiang, Wenlong; Zhou, Lihong; Zeng, Qingle
Abstract : Tosylhydrazones are a kind of labile and highly reactive compounds, which are apt to be transformed into reactive diazo compounds and then into extremely reactive carbenes under the basic condition. In order to fulfil the valuable C‐N coupling reaction, diaryliodonium salts are evaluated and prove to be a class of efficient electrophiles. The reaction with ligand‐free copper salt as catalyst shows a wide range of substrate scope. A plausible mechanism is proposed. Abstract : Tosylhydrazones are a kind of labile and highly reactive compounds under basic conditions. Diaryliodonium salts are found to be an efficient electrophile for C‐N coupling reaction under basic condition. The ligand‐free copper‐catalyzed reaction shows a wide range of substrate scope.